Media and Cultural Industries: a Socioeconomic Approach - Bernard Miège (Universidad Autónoma de Baja California, 2008)
<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">This article reviews the discussion that initiated in the 70's about the relationship between communication and information phenomena, and decisions in the economic field. This discussion, according to Miège, has been undertaken from different perspectives that have placed economy and technology at the core of the analysis. The author proposes to study these phenomena through an interdisciplinary methodology, based on the theories of <em style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff;">cultural industries<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;"> and the<em style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff;">political economy of communication<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">. Miège argues that with industrialization of media contents, consumer product access is no longer direct and products may be available without any cost to the consumer, since the cost of informational and cultural products is paid through advertising. However, this new environment creates certain problems, such as regulating the sale of these products, turning them and their symbolic content as marketable goods or hiring intellectual and artistic workers under an unregulated framework. He also discusses a double economic operation: the sale of products to publicists, and the sale of the same products by the publicists according to the market demand. The last part of the article is an analysis made by the author on the consequences that economic changes might have on cultural industries, because of their current need to keep cooperation relationships with technological industries, as well as connections with large financial groups.